CONSTRUCTION OF ECONOMIC MODELS AND THEIR USE FOR FORECASTING - Бородіна, Олена; Довгань, Максим (SWorldJournal, 2024)
The article is devoted to the use of econometric models for forecasting economic processes. The content of the economic model, types of economic models as objects of economic-mathematical modeling are determined. The article examines the main types of eco